What affects vocational competencies in German post-secondary VET? - Velten, Stefanie [Verfasser] (My University, 2017)
"This paper aims at investigating the role of cognitive and non-cognitive impact factors on vocational knowledge at the beginning of postsecondary training in a German sample. Although the relevance of post-secondary training for the future economy is documented, little is known about competence development after initial VET in Germany. Therefore, the study seeks to highlight vocational knowledge acquisition that is crucial for future job performance. Referring to Ackerman's PPIK theory, the roles of fluid intelligence, prior knowledge, and achievement motivation are investigated. In addition, the relevance of work experience is addressed using different measurements." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.2 Bildungsverhalten und -verläufe; S 1.5.2 Berufliche Weiterbildung; Aufstiegsfortbildung; Höhere Berufsbildung; Beruflicher Aufstieg; Kompetenzentwicklung; Kognitive Fähigkeit; Weiterbildungsmotivation; Einflussfaktor; Wissenserwerb; Elektrotechnik